k-62=2k-69

Simple and best practice solution for k-62=2k-69 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k-62=2k-69 equation:



k-62=2k-69
We move all terms to the left:
k-62-(2k-69)=0
We get rid of parentheses
k-2k+69-62=0
We add all the numbers together, and all the variables
-1k+7=0
We move all terms containing k to the left, all other terms to the right
-k=-7
k=-7/-1
k=+7

See similar equations:

| 12h+41=11h+57 | | 15z+2=8z+93 | | 3+6a=15+4a | | 9p+17=16p-88 | | 8q+97=18q-93 | | 3(-3x+2)=-(2x-4) | | 2n+10=n+81 | | 13g-63=9g-43 | | 7w+54=80w-92 | | 14r+7=59r-38 | | 13=4v+3+6v | | 2(7)+2(x+4)=70 | | -97=-8(1+2k)=7 | | 2x-12+3x=13 | | 7y=+2y | | 6^(6x^2-3x)-3*2^(6x^2-3x)+3=3^(6x^2-3x) | | x+115=110x | | 15-7=x-9 | | (5x-5)(3x+7)=0 | | 65x^2-96x=0 | | 2x/3-11=37 | | 1200=8x−400 | | 1,200=8x−400 | | 33+6x=6(x+12) | | X=1/2*30+2x-30 | | 3+3x=372 | | -5p-7=-15-4p | | 5(x-2)=30+3x | | 5x+8=7x–72 | | F(x)=–(x–4)2–3 | | 5(x/4-1-10)=1/2(3x-1/2) | | 11y-2=y+5;y=3/5 |

Equations solver categories